An Analysis Of Drug Planning Using ABC Index Method Critical In The Pharmacy Installation Public Hospital Royal Prima Marelan - Disti Amanda Putri; Ermi Girsang; Sri Lestari Ramadhani Nasution (Jurnal Scientia, 2024)
Needs planning is an activity to determine the quantity and period of procurement of pharmaceuticals, medical devices and disposable medical materials in accordance with the results of selection activities to ensure that the criteria for the right type, right quantity, right time and efficiency are met. The purpose of the research is to analysed drug planning with ABC critical index method at the Pharmacy Installation of Royal Prima Marelan Hospital. Type This study is a combination of qualitative and quantitative research at the Pharmacy Installation at Hospital.Royal Prima Marelan. The qualitative sample of the study was 3 people and the data source was the drug needs plan. The research instrument used a questionnaire. The results of this study with ABC analysis of the critical index value of group A usage were 30 items (51%), group B obtained 23 items (39%) and group C obtained 8 items (9%). Based on the calculation with ABC analysis of the critical index of investment value, group B obtained 2 items (3%) of the total items and group C obtained 57 items (97%) of the total items in the Pharmacy Installation. Based on the calculation with ABC analysis of the critical index of investment value, group B obtained 2 items (3%) of the total items and group C obtained 57 items (97%) of the total items in the Pharmacy Installation. The results of qualitative research on drug planning at the Pharmacy Installation of Hospital. Royal Prima Marelan used the consumption method, namely looking at the average use of drugs in the previous 3 months, at the time of service there were still frequent stock outs of drugs. It is necessary to prepare and evaluate a drug requirement plan (RKO) which is carried out every month as a basis for planning drug requirements and/or can use methods to analysed drug requirements that are efficient, effective and appropriate.